INTEGRASI TEORI KONSTRUKTIVISTIK DAN NILAI TA’DIB DALAM PEMBELAJARAN PAI BERBASIS MODERASI BERAGAMA DI PONPES MANSYAUL ULUM CONGKOP NAGASARI - Noris Soleh; Moh. Nurullah; Siful Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
With an emphasis on the synthesis of contemporary educational methods and traditional Islamic scholarly traditions, this study seeks to investigate the integration of constructivist theory and ta'dib values in Islamic Religious Education (PAI) learning based on religious moderation in Islamic boarding schools (AS). This study uses a case study design, field research, and qualitative methodology. Participant observation, in-depth interviews, and documentation were used to collect data. An interactive analytical model was then used to cycle the data through the steps of data reduction, data presentation, and drawing conclusions. The findings indicate that the planning, implementation, and assessment phases of the PAI learning process have begun to integrate constructivism and ta'dib. Through discussion techniques, case studies, and problem-based learning, the constructivist approach encourages critical thinking and active student engagement, while the ideals of Ta'dib provide an ethical foundation for shaping manners, morality, and spirituality. It has been shown that this integration improves students' religious and contextual understanding and fosters inclusive, tolerant, and moderate attitudes. However, several obstacles remain in the implementation of this integration, including teachers' lack of pedagogical knowledge, a hierarchical learning culture, and a lack of supporting resources. Consequently, initiatives are needed to improve teacher skills, create an integrative curriculum, and establish teaching methods that remain grounded in the ideals of Ta'dib. This study demonstrates that a relevant and strategic learning model for the advancement of Islamic education in Islamic boarding schools (pesantren) is formed through a combination of constructivist theory and the principles of ta'dib. In addition to helping shape a generation that is knowledgeable, polite, and savior in various matters, this model is also capable of addressing the challenges of contemporary education.